2002
DOI: 10.1093/annonc/mdf065
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine (Xeloda®) in combination with oxaliplatin: a phase I, dose-escalation study in patients with advanced or metastatic solid tumors

Abstract: Oral capecitabine with i.v. oxaliplatin is a feasible combination regimen that shows promising antitumor activity in patients with colorectal cancer. There is an ongoing, phase II study to further characterize the safety and efficacy of this combination as first-line therapy for metastatic colorectal cancer, using the recommended dose identified in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
55
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 23 publications
3
55
0
Order By: Relevance
“…Cassidy et al (2004) reported the results of a phase II study of oxaliplatin plus capecitabine (XELOX) as a firstline therapy in patients with colorectal cancer (Díaz-Rubio et al, 2002). Oxaliplatin (130 mg m À2 ) was administered on day 1 and capecitabine (2000 mg m À2 day À1 ) for 14 days with a 1-week rest, every 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cassidy et al (2004) reported the results of a phase II study of oxaliplatin plus capecitabine (XELOX) as a firstline therapy in patients with colorectal cancer (Díaz-Rubio et al, 2002). Oxaliplatin (130 mg m À2 ) was administered on day 1 and capecitabine (2000 mg m À2 day À1 ) for 14 days with a 1-week rest, every 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where sudden and severe thrombocytopaenia is observed, type II allergic reaction to oxaliplatin should be considered and definitive withdrawal is strongly suggested (Maindrault-Goebel et al, 2001). A phase I study of XELOX with 130 mg m À2 of oxaliplatin tri-weekly has also shown a relatively higher incidence of grade 3 thrombocytopaenia in 22% (Díaz-Rubio et al, 2002), but only 4% during phase II with weekly assessment of CBC (Cassidy et al, 2004). Thrombocytopaenia of SOX should be evaluated in the future phase II or III studies with a larger number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…These include continuous capecitabine (7 days per week) with oxaliplatin given on days 1 and 29 (Glynne-Jones et al, 2006c), continuous capecitabine (5 days per week) with weekly doses of oxaliplatin (Machiels et al, 2005;Rutten et al, 2006) and discontinuous capecitabine (days 1 -14 and 22 -35) with oxaliplatin on days 1, 8, 22 and 29 (Roedel et al, 2003(Roedel et al, , 2007. The aim of the present multicentre phase II study was to evaluate the efficacy, tolerability and feasibility of preoperative capecitabine plus oxaliplatin in combination with radiotherapy as described by Roedel et al (2003Roedel et al ( , 2007, and to investigate the contribution of an additional single cycle of neoadjuvant capecitabine and oxaliplatin (XELOX regimen) (Díaz-Rubio et al, 2002;Cassidy et al, 2004) before the start of radiotherapy.…”
mentioning
confidence: 98%
“…However, G-CSFs were prescribed appropriately in intermediate-and low-risk patients at our institution. In previous study inappropriate prescribing of G-CSFs increase FN episodes with lung and colorectal cancer on chemotherapy regimens receiving G-CSFs, the probability of high, intermediate and low risk FN was 17%, 18% and 10%, respectively; and 96% of G-CSFs use were not based on guidelines [25][26][27][28][29][30][31][32][33][34][35][36]. In our study, the appropriateness of G-CSFs use was not associated with FN incidence in patients received chemotherapy regimens with high risk of FN potential.…”
Section: Discussionmentioning
confidence: 95%